2014
DOI: 10.1007/s13277-013-1557-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair gene ERCC1 polymorphisms may contribute to the risk of glioma

Abstract: Polymorphisms in excision repair cross-complementing rodent repair deficiency complementation group 1 (ERCC1) gene have been shown to affect individual susceptibility to glioma, though studies have yielded conflicting results. This meta-analysis aims to derive a more precise estimation of the association between ERCC1 C8092A and C118T polymorphisms and glioma risk. A literature search of PubMed, Embase, Web of Science, Cochrane Library, and CBM databases was conducted to identify all eligible studies published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Almost at the same time, Yuan et al associated rs11615 and rs3212986 with glioma and observed a main effect particularly in Asian [45]. The rs3212986 association was also replicated in another metaanalysis where multiple DNA repair genes were included [46].…”
Section: Discussionmentioning
confidence: 82%
“…Almost at the same time, Yuan et al associated rs11615 and rs3212986 with glioma and observed a main effect particularly in Asian [45]. The rs3212986 association was also replicated in another metaanalysis where multiple DNA repair genes were included [46].…”
Section: Discussionmentioning
confidence: 82%
“…Genetic factors, such as single nucleotide polymorphisms (SNPs), play an important role in modifying glioma susceptibility, such as SNPS in XRCC1, ERCC1, interleukin-8, and VEGF genes (Jiang et al, 2013;Yuan et al, 2014;Liu et al, 2015;Wang et al, 2015). The rs13181 polymorphism of ERCC2 is a T to G substitution at the 751 locus, which may alter the enzymatic activity of the encoded protein.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2014) conducted a meta-analysis with 11 case-control studies, but they did not find any association between the ERCC1 rs3212986 polymorphism and development of lung cancer. Yuan et al (2014) also conducted a meta-analysis with seven studies, and reported that the ERCC1 rs3212986 polymorphism correlated with the risk of non-glioblastoma multiforme. The association between the ERCC1 rs3212986 polymorphism and the risk of pancreatic cancer has been reported in only one previous study (McWilliams et al, 2008).…”
Section: Discussionmentioning
confidence: 99%